Food Preference of Long-tailed Macaques (Macaca fascicularis Raffles 1821) in IPB Dramaga Campus (Indonesian Journal of Primatology, 2022)
Long-tailed macaques (Macaca fascicularis) will expand their daily home range to obtain good and plentiful food sources, thus often causing conflict. Identification of long-tailed macaque feed preferences needs to be done as a form of minimizing conflict. This research aims to identify the type of feed and feed preference, and also to analyze the daily activity of long-tailed macaques. The research was conducted by vegetation analysis and field observation of the daily activities of long-tailed macaques. The results of this research showed that there were 22 types of feed plants and 2 types of non-plant feeds. Long-tailed macaques are kind of fructivore animals but will be opportunistic omnivores if the availability of fruits decreases. Long-tailed macaques are more interested to eat fruit, especially Belimbing Bintang fruit (Averrhoa carambola), Matoa fruit (Pometia pinnata), and Jabon fruit (Neolamarckia cadamba).